2020
DOI: 10.3201/eid2604.190840
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of Azole-Resistant Aspergillus fumigatus Clinical Isolates, Taiwan1

Abstract: Isolation of Brucella melitensis biovar 3 from a chamois (Rupicapra rupicapra) in the southern French Alps. J Wildl Dis. 8. Maquart M, Le Flèche P, Foster G, Tryland M, Ramisse F, Djønne B, et al. MLVA-16 typing of 295 marine mammal Brucella isolates from different animal and geographic origins identifies 7 major groups within Brucella ceti and Brucella pinnipedialis. BMC Microbiol. 2009;9:145. https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 10 publications
6
28
1
Order By: Relevance
“…More recently, the reports of A. fumigatus azole resistant isolates, without Cyp51A modifications, indicate that there are other novel mechanisms mediating resistance to azole drugs [ 11 , 12 ]. These studies have reported roles in azole resistance of other genes from the ergosterol biosynthesis pathway, including hmg1 [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], erg6 [ 15 , 17 ], some transcriptional factors [ 20 , 21 , 22 ], hapE [ 23 ] or overexpression of drug efflux pumps [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the reports of A. fumigatus azole resistant isolates, without Cyp51A modifications, indicate that there are other novel mechanisms mediating resistance to azole drugs [ 11 , 12 ]. These studies have reported roles in azole resistance of other genes from the ergosterol biosynthesis pathway, including hmg1 [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], erg6 [ 15 , 17 ], some transcriptional factors [ 20 , 21 , 22 ], hapE [ 23 ] or overexpression of drug efflux pumps [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within our study, the E105K and the S541G mutation were also found in two (5%) and one (3%), respectively, of 39 isolates with a triazole WT phenotype. The S541G and H564Y hmg1 mutations located likewise outside the SSD, have also been reported in non-resistant isolates [ 8 , 11 ]. This a major issue, as it raises the probability that these mutations located outside the SSD most likely do not confer resistance and that other mechanisms are responsible for the observed resistant phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mutations in the 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase -encoding gene ( hmg1 ), were described and associated with triazole-resistance in a number of clinical A. fumigatus isolates [ 8 , 9 , 10 , 11 , 12 ]. Like the cyp51A gene, the hmg1 gene is involved in the ergosterol production pathway [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…When haematological (ESR, CRP, fungal G test, etc.) and imaging examinations indicate Aspergillus spondylitis, CT-guided puncture biopsy should be performed as soon as possible to confirm the diagnosis and guide antibacterial treatment [ 19 ]. Compared with intraoperative biopsy, CT-guided biopsy is less invasive and has a quicker recovery time, but the number of specimens is insufficient.…”
Section: Discussionmentioning
confidence: 99%